Information technology capability, supply chain practices and leagility: A systematic literature review - Mustafa Al Dirawi, Ammar Nazar; Khudari, Mohamed; Salina, Daud (Creative Publishing House, 2024)
To cope with the unpredictabilities of the ever-changing modern business environment, businesses need strategies that help them maintain efficiency and flexibility. Leagility, an amalgam of “lean” and “agile”, enables them to integrate both advantages. Lean strategy improves efficiency by minimizing waste and costs, while agile strategy allows businesses to rapidly adapt to market trends. Despite its importance for businesses, leagility has received little attention in the literature. Moreover, research on the relationship between IT capability, supply chain practices and leagility, is limited. This systematic literature review addresses these concerns. Based on an analysis of 30 related articles, this study finds increasing interest in the topic, but notably in China, India and the US, with fewer studies from other developing countries. Moreover, most leagility studies are quantitative. These findings challenge previous studies claiming that a majority of the studies are qualitative. Additionally, a sound majority of leagility studies relate to the manufacturing sector, which questions other studies expressing the need for more research on this sector. Further conclusions from the present study indicate that efficiency, effectiveness, responsiveness, and flexibility are the most important dimensions of leagility for successful supply chain performance. Also, leagility requires IT capability, comprising especially IT infrastructure, IT human resources, and IT integration. Also, to help businesses adjust swiftly to market changes, while being efficient, information sharing, information quality, strategic supplier partnership, and postponement, are essential to leagile supply chain practices. This study suggests the need for further research in understudied locations on leagility, IT capability, and supply chain practices, using qualitative and mixed-method approaches to fully comprehend the issue. Studying how emerging technologies and global crisis influence these interactions may also help in developing more robust, flexible and successful supply chain strategies.